Primary structure of prion protein may modify scrapie isolate properties. - Carlson, G A (1989)
Scrapie is an infectious neurodegenerative disease caused by unusual pathogens called prions, in which no scrapie-specific nucleic acid has been detected to date. The only known component of the prion is the scrapie isoform of prion protein (PrPSc), which is encoded by a host gene (Prn-p). Isolates of scrapie agent were prepared by passage of infectivity through inbred strains of mice that differ in scrapie incubation time and produce PrPSc molecules differing by two amino acids. Both the length and variability of the incubation period were increased by inocula containing allogeneic PrPSc. For example, Prn-pb I/Ln mice inoculated with scrapie isolate passaged through Prn-pa NZW mice had incubation times of 283 +/- 21 days compared with a 193 +/- 6 day incubation time seen with isolate passaged once through isologous I/Ln mice. No further shortening of incubation time was observed following further isologous passage. NZW incubation times were prolonged by inoculation with prions from I/Ln mice. Results from (NZW x I/Ln)F2 mice and from using inocula from donors isologous for Prn-p but otherwise allogeneic with respect to the recipient suggest that the primary structure of PrPSc is responsible for these incubation time results. Incubation times in (NZW x I/Ln)F1 mice were constant regardless of the passage histories of the scrapie isolates and were equivalent to those of I/Ln mice inoculated with I/Ln prions, contending that prolongation of scrapie incubation time by the prion incubation time gene Prn-i is fully dominant. I/Ln incubation times longer than those in F1 hybrids may reflect a reduced efficiency of allogeneic PrPSc in initiating disease. Although some investigators propose that differences in behavior among scrapie isolates reflect host selection and argue for a nucleic acid genome, we suggest that the variation observed among our scrapie isolates is epigenetic, reflecting host-directed differences in the amino acid sequence of PrPSc.